PENERAPAN METODE ZERO WASTE FASHION DESIGN PADA TENUN SENGKANG UNTUK BUSANA DEMI-COUTURE - Nurfadhilah Nadir; Faradillah Nursari; Marissa Cory Agustina Siagian (Serat Rupa: Journal of Design, 2022)
Zero waste is a concept applied by industry by maximizing the use of fabrics which aims to reduce textile waste. One of the zero-waste methods that can maximize the dimensions of the fabric is the geometric technique. The zero-waste method can be applied to demi-couture clothing which produces quite a lot of waste with a total of 20% pre-production waste. Demi couture includes clothing that requires high craftmanship and is specially made with a limited number of productions Therefore, the application of Sengkang weaving can be used as a demi-couture dress because of the quality and price of the Sengkang weaving are relatively high. The use of the craft on the Sengkang weaving must also be maximized. Therefore, the Sengkang weaving needs to maximize the dimensions of the fabric using the concept of zero waste fashion design. The purpose of this research is an effort to optimize the zero-waste pattern on clothing for the sake of couture by using woven as a zero-waste fashion design product. The research method is to use a qualitative method with an exploration of the pattern of zero waste fashion design. The final result of this research is a fashion design for the sake of couture with the application of Sengkang woven fabric using the zero waste fashion design method.